Decided Ratio on Religious Court Decision No. 701/Pdt.G/Pa/Sky Concerning Mandatory will for Non-Muslim - Mochamad Umar Saktiaji; Sihabudin Sihabudin; Fathul Laila (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aims of the study to find out Decided Ratio on Religious Court Decision No. 701/Pdt.G/Pa/Sky Concerning Mandatory Will for Non-Muslim. This study used qualitative research. Based on the description of the discussion in the previous chapter, it can be concluded that the research results are as follows: a.Mandatory wills for non-Muslims in the perspective of Islamic law from among scholars have religious opinions, but according to contemporary Islamic legal theory. b. Compulsory will law against non-Muslims in a positive legal perspective is not regulated normatively in a clear formulation, both in the Civil Code (KUHPdt) and in the Compilation of Islamic Law (KHI). Its application is based on jurisprudence.